(untitled) (Innovative professional education, 2023)
The influence of anthropogenic factors on the Black Sea coast and coastal waters has led to a situation of ecological crisis. Ports and water transport make a significant contribution to the deepening of the environmental crisis. The complexity of the ecological situation dictates the need of minimization the ecological consequences caused by industrial activity, hydrotechnical structures, sewage pollution, natural landfills, and the fleet operating on the river. The article describes the environmental protection activities of PJSC "Ukrainian Danube Shipping" which is carried out jointly with the international Danube Commission, and the cooperation of the UDS with educational institutions in the field of environmental training of future managers of the maritime industry.